2013
DOI: 10.1111/sdi.12093
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nervous System Function and Dysfunction in Chronic Hemodialysis Patients

Abstract: Adequate sympathetic nervous system activation is essential for the compensatory mechanisms of blood pressure maintenance during the hemodialysis (HD) procedure. Chronic sympathetic nervous system overactivity, however, may lead to the development of hypertension and cardiovascular disease in HD patients. The present review focuses on recent findings on the sympathetic nervous system activity in these patients. Sympathetic overactivity has been demonstrated directly by muscle sympathetic nerve activity recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 142 publications
5
73
1
9
Order By: Relevance
“…Our findings showed that patients with kidney disease have improved cardiac autonomic regulation during hemodialysis, supporting Rubinger et al [10] in which they reported that hemodialysis treatment induced a lower risk of sudden death or other cardiovascular aggravating event and consequently better control autonomic in chronic renal disease patients [7].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our findings showed that patients with kidney disease have improved cardiac autonomic regulation during hemodialysis, supporting Rubinger et al [10] in which they reported that hemodialysis treatment induced a lower risk of sudden death or other cardiovascular aggravating event and consequently better control autonomic in chronic renal disease patients [7].…”
Section: Discussionsupporting
confidence: 77%
“…During hemodialysis, adequate stimulation of sympathetic nervous system is crucial for the beginning and preservation of compensatory mechanisms to maintain blood pressure, especially peripheral vasoconstriction and an increase in heart rate [7,10].The results found in our studysuggest a lower risk of a negative cardiovascular event during the hemodialysis procedure.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Adequate sympathetic nervous system activation is essential for hypotension compensatory mechanisms, which help maintain blood pressure during HD sessions. 19,20 We found that HD had no statistically significant effect on IOP or CCT. However, the effect of HD on IOP is somewhat controversial, with some studies reporting significant IOP changes during HD sessions.…”
Section: Discussionmentioning
confidence: 71%
“…It refers to Parkinson's disease, Alzheimer's dementia 59,60 , haematological malignancies (amyloidosis) (ref. 61 ), patients in chronic hemodialysis 62 , systemic inflammatory diseases 63 . As a diagnostic auxiliary tool HRV can be used in testing the patients with syncope 64 , sleep apnea 65 , in psychiatry in diagnosis and during treatment of depression 66 .…”
Section: Reproducibility Of Hrv Measurementsmentioning
confidence: 99%